A UV detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction and its preparation method

By constructing the FTO/TiO2:PEO/MAPbCl3 heterojunction, the challenges of existing one-dimensional wide bandgap semiconductor ultraviolet detectors in dark current control and array preparation are solved, and the ultraviolet detection effect with high responsiveness and low dark current is achieved, which is suitable for large-scale production.

CN115472745BActive Publication Date: 2025-04-25JILIN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211039175.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-29
Publication Date
2025-04-25
Estimated Expiration
2042-08-29

AI Technical Summary

Technical Problem

The existing one-dimensional wide bandgap semiconductor UV detectors have challenges in improving device performance and large-area array preparation, especially the difficulty in effectively controlling dark currents and noise, limiting their wider applications.

Method used

UV detector based on FTO/TiO2:PEO/MAPbCl3 heterojunction is adopted to build a composite heterojunction, enhance the built-in electric field, adjust the surface work function of electron transmission in the photosensitive layer, and reduce the contact barrier between the active layer and the electrode, thereby improving the electron extraction capability and carrier migration efficiency.

Benefits of technology

It realizes high responsiveness and low dark current ultraviolet detectors, which can effectively detect UVA ultraviolet rays in the range of 300 to 400 nm, improves the overall performance of the device, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115472745B_ABST
    Figure CN115472745B_ABST
Patent Text Reader

Abstract

A UV detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction and a preparation method thereof, belonging to the field of UV photoelectric detection technology. The detector is composed of an FTO substrate, a TiO2 one-dimensional nanorod array film, a PEO interface modification layer, a polycrystalline perovskite MAPbCl3 film and an Ag electrode from bottom to top. The TiO2 one-dimensional nanorod array film, the PEO interface modification layer and the polycrystalline perovskite MAPbCl3 film constitute the TiO2:PEO / MAPbCl3 heterojunction photosensitive layer, and the UV light to be measured is incident from one side of the FTO substrate. The present invention enhances the built-in electric field by constructing a composite heterojunction, effectively adjusts the surface work function of electron transmission in the photosensitive layer, reduces the contact barrier between the active layer and the electrode, thereby enhancing the electron extraction ability, effectively improving the migration efficiency of the carriers inside the device, and has an excellent effect of having a high response to UV light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ultraviolet photoelectric detection, and specifically relates to an ultraviolet detector based on a FTO / TiO2:PEO / MAPbCl3 heterojunction and a preparation method thereof. Background Art

[0002] Ultraviolet rays are a general term for electromagnetic waves with a wavelength of 10nm to 400nm, which are mainly divided into the following bands: long-wave ultraviolet rays (UVA for short) are about 320 to 400nm, medium-wave ultraviolet rays (UVB for short) are about 280 to 320nm, and short-wave ultraviolet rays (UVC for short) are about 200 to 280nm. Among them, ultraviolet light in the UVA band belongs to the low-energy ultraviolet radiation area, accounting for about 90% of the total ultraviolet radiation in the sunlight reaching the surface of the earth. For the human body, excessive UVA exposure may cause erythema on the skin, and in more serious cases, it may even penetrate the dermis, induce the production of melanin, and cause skin aging and darkening.

[0003] Organic / inorganic lead halide perovskite materials (MAPbX3, MA=CH3NH3 + , X=Cl-, Br- or I - ), due to its impressive optoelectronic properties (such as directly adjustable band gap, strong light absorption ability, high carrier mobility, long carrier diffusion length, etc.), it has become a competitive candidate for the next generation of photovoltaic devices. Among them, the CH3NH3PbCl3 (MAPbCl3) material with a band gap of 3.11eV can only collect radiation below 400nm, which is an ideal choice for long-wave ultraviolet UVA photodetection. TiO2, as a wide-bandgap oxide semiconductor material, has a bandgap width of 3.0eV, has good absorption properties for ultraviolet light below 400nm and has high chemical stability. In addition, since FTO conductive glass (fluorine-doped SnO2 conductive glass) can absorb radiation below 300nm, the FTO / TiO2:PEO (polyethylene oxide) / MAPbCl3 heterojunction ultraviolet detector produced in this application can effectively detect ultraviolet light with a wavelength range of 300-400nm, and accurately realize UVA monitoring.

[0004] In recent years, domestic and foreign research has shown that one-dimensional wide bandgap semiconductor ultraviolet detectors have many advantages such as stable operation, high responsiveness, and fast response speed, showing the potential to replace more traditional ultraviolet detectors based on three-dimensional materials and two-dimensional thin film materials. One-dimensional wide bandgap semiconductor materials have high carrier transmission efficiency and photoelectric conversion efficiency, so one-dimensional material ultraviolet detectors generally have large photocurrent and photoresponsivity. However, due to the large number of traps and defects in the one-dimensional material body, it is difficult to effectively control the dark current and noise of one-dimensional material devices, and the device performance cannot be improved comprehensively and balanced. At the same time, one-dimensional materials also lack effective means in large-area and array preparation, which limits their wider promotion and application. Therefore, on the basis of one-dimensional wide bandgap semiconductor materials and devices, using reasonable and simple methods to improve and innovate in composite material preparation and device physical mechanism, so as to achieve the improvement of device comprehensive performance and the preparation of arrayed devices, has become a hot spot and mainstream direction of research in the field of ultraviolet detection technology. Summary of the invention

[0005] The purpose of the present invention is to provide an ultraviolet detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction and a preparation method thereof. The method is simple and easy to implement, has few steps, low cost, low equipment requirements, has a high response to ultraviolet light, is suitable for mass production, and has important application value. At the same time, by constructing a composite heterojunction, the built-in electric field is enhanced, the surface work function of electron transmission in the photosensitive layer is effectively adjusted, and the contact barrier between the active layer and the electrode is reduced, thereby enhancing the electron extraction ability and effectively improving the migration efficiency of the carriers inside the device.

[0006] The technical solution of the present invention is:

[0007] The invention discloses an ultraviolet detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction, which is characterized by being composed of, from bottom to top, an FTO substrate, a TiO2 one-dimensional nanorod array film grown on the FTO, a PEO interface modification layer spin-coated on the TiO2 nanorod array film, a polycrystalline perovskite MAPbCl3 film spin-coated on the PEO interface modification layer, and an Ag electrode prepared on the polycrystalline perovskite MAPbCl3 film; the TiO2 one-dimensional nanorod array film, the PEO interface modification layer and the polycrystalline perovskite MAPbCl3 film constitute a TiO2:PEO / MAPbCl3 heterojunction photosensitive layer; and ultraviolet light to be detected is incident from one side of the FTO substrate. Among them, the thickness of the FTO substrate is 2 to 3 mm, the thickness of the TiO2 one-dimensional nanorod array film is 2 to 3 μm, the thickness of the PEO interface modification layer is 20 to 30 nm, the thickness of the polycrystalline perovskite MAPbCl3 film is 300 to 500 nm, and the thickness of the Ag electrode is 1 to 3 mm.

[0008] The method for preparing a UV detector based on a FTO / TiO2:PEO / MAPbCl3 heterojunction of the present invention comprises the following steps:

[0009] (1) Substrate processing

[0010] The FTO substrate is sequentially immersed in acetone, ethanol, and deionized water for ultrasonic treatment for 10 to 20 minutes, then blown dry with nitrogen, and then placed in an ultraviolet ozone environment for treatment for 10 to 20 minutes to obtain a clean substrate;

[0011] (2) Preparation of TiO2 one-dimensional nanorod array films

[0012] At room temperature, add 8-15 mL of toluene to a reaction kettle, measure 0.5-1.5 mL of tetrabutyl titanate and drip it dropwise, and at the same time shake the reaction kettle to disperse the tetrabutyl titanate in the toluene; measure 0.1-0.3 mL of titanium tetrachloride and slowly add it below the liquid surface of the above solution to prevent the titanium tetrachloride from volatilizing and to make it evenly dispersed; then measure 0.5-1.5 mL of hydrochloric acid with a mass fraction of 36-38%, and drip it dropwise into the above solution; the FTO surface of the substrate cleaned in step (1) is tilted downward and placed in the reaction kettle and immersed below the liquid surface of the solution, and it is fixed, the reaction kettle is sealed, and a hydrothermal reaction is carried out at 150-200° C. for 4-8 hours. After naturally cooling to room temperature, the substrate is taken out and naturally dried in air at room temperature, thereby obtaining a 2-3 μm thick TiO2 one-dimensional nanorod array film on the FTO surface;

[0013] (3) Interface modification of TiO2 one-dimensional nanorod array films by PEO

[0014] The device obtained in step (2) is irradiated in ultraviolet ozone for 10 to 30 minutes to perform hydroxylation treatment on the surface of the TiO2 one-dimensional nanorod array film; 0.02 to 0.12 g of PEO is dissolved in 10 to 50 mL of deionized water and ultrasonicated until completely dissolved; the PEO solution is spin-coated on the surface of the hydroxylated TiO2 one-dimensional nanorod array film at a spin-coating speed of 1500 to 2500 rpm for 20 to 40 seconds; then, the PEO solution is spin-coated at 80 to 100° C. for 5 to 10 minutes, and the FTO substrate is cooled to room temperature, thereby obtaining a 20 to 30 nm thick PEO interface modification layer on the surface of the TiO2 one-dimensional nanorod array film;

[0015] (4) Preparation of MAPbCl3 precursor solution

[0016] At room temperature, 0.5-2 mL DMSO (dimethyl sulfoxide) and 0.5-2 mL DMF (N,N-dimethylformamide) are respectively weighed and mixed, and 0.1-0.2 g MACl (methylamine chloride) is weighed and added thereto and stirred for 10-30 minutes; then 0.4-0.6 g PbCl2 (lead chloride) is weighed and added thereto and stirred for 20-40 minutes until the solution becomes completely transparent, thereby obtaining a MAPbCl3 precursor solution;

[0017] (5) Preparation of TiO2:PEO / MAPbCl3 heterojunction

[0018] Spin coating a MAPbCl3 precursor solution on the surface of the PEO interface modification layer to form a 300-500 nm thick polycrystalline perovskite MAPbCl3 film, the spin coating speed is 2000-3500 rpm, and the spin coating time is 20-40 seconds; then adjust the speed to 1000-1500 rpm, and immediately spin coat 40-50 μL of toluene as an anti-solvent on the polycrystalline perovskite MAPbCl3 film, and the spin coating time is 3-5 seconds; after drying at 70-100° C. for 4-8 hours, cool the substrate to room temperature, thereby obtaining a TiO2:PEO / MAPbCl3 heterojunction on the surface of the FTO substrate;

[0019] (6) Preparation of Ag electrode

[0020] Ag conductive glue is dropped on the FTO and polycrystalline perovskite MAPbCl3 layers as electrodes, and then dried at 70-120°C for 8-20 minutes to obtain a UV detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction. Its structure is as follows Figure 1 shown. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 : A schematic diagram of the structure of the ultraviolet photodetector prepared by the present invention;

[0022] Figure 2 : XRD pattern of TiO2 one-dimensional nanorod array film prepared by the present invention;

[0023] Figure 3 : XRD pattern of the polycrystalline perovskite MAPbCl3 film prepared by the present invention;

[0024] Figure 4 : SEM image of the TiO2 one-dimensional nanorod array film prepared by the present invention;

[0025] Figure 5 : SEM image of TiO2:PEO / MAPbCl3 heterojunction prepared by the present invention;

[0026] Figure 6: UV-visible absorption graphs of FTO / TiO2:PEO and FTO / TiO2:PEO / MAPbCl3 photosensitive layers prepared by the present invention;

[0027] Figure 7 : The current-voltage characteristic curve of the ultraviolet light detector based on the FTO / TiO2 one-dimensional nanorod array structure prepared by the present invention;

[0028] Figure 8 : The current-voltage characteristic curve of the ultraviolet light detector based on the FTO / TiO2:PEO structure prepared by the present invention;

[0029] Fig. 9 : The current-voltage characteristic curve of the ultraviolet light detector based on FTO / TiO2:PEO / MAPbCl3 structure prepared by the present invention.

[0030] like Figure 1 As shown, ultraviolet light is irradiated from one side of the FTO substrate onto the ultraviolet light detector based on the FTO / TiO2:PEO / MAPbCl3 heterojunction photosensitive layer to generate photocurrent. The names of the components are: FTO substrate 1, TiO2 one-dimensional nanorod array film 2, PEO interface modification layer 3, polycrystalline perovskite MAPbCl3 film 4, Ag electrode 5, and lead 6 connecting the Ag electrode to the external power supply.

[0031] like Figure 2 As shown, the XRD pattern of the TiO2 one-dimensional nanorod array film corresponds to PDF card 76-1938, and the TiO2 nanorods obtained in the experiment are standard rutile TiO2.

[0032] like Figure 3 As shown in the XRD diagram of the polycrystalline perovskite MAPbCl3 powder, it can be seen that the diffraction peak of the crystal is obviously prominent, indicating that the prepared material has high crystal quality and distinct crystal particles.

[0033] like Figure 4 As shown, it shows that the TiO2 one-dimensional nanorod array film grows vertically on FTO and is uniform and dense.

[0034] like Figure 5 As shown, it shows that the polycrystalline perovskite MAPbCl3 is uniformly formed on the TiO2 one-dimensional nanorod array film. The left side is the TiO2 one-dimensional nanorod array, and the right side is the polycrystalline perovskite MAPbCl3 film.

[0035] like Figure 6As shown, the absorbance in the visible light region above 400nm and the absorbance in the region below 300nm are lower than those in the UVA region of 300-400nm, indicating that the device works in the UVA region of 300-400nm, and the absorption range of the FTO / TiO2:PEO / MAPbCl3 heterojunction device is larger and closer to 400nm than that of the FTO / TiO2:PEO device.

[0036] like Figure 7 As shown in the inner figure, the current-voltage curve of the ultraviolet detector based on the FTO / TiO2 structure in the linear coordinate system shows a rectification characteristic. When TiO2 and FTO form a heterojunction, the conduction band position of TiO2 is higher than the conduction band position of FTO, so the free electrons in TiO2 flow to FTO, forming a space charge region on one side of TiO2, thereby forming a Schottky junction between TiO2 and the FTO surface; Figure 7 As shown, in the logarithmic coordinate system, the light-dark suppression ratio of the ultraviolet light detector based on the FTO / TiO2 structure under positive and reverse bias is less than one order of magnitude, indicating that the device has a certain ultraviolet light detection capability, but the dark current and light-dark suppression ratio need to be improved.

[0037] like Figure 8 As shown in the figure, the current-voltage characteristics of the ultraviolet light detector based on the FTO / TiO2:PEO structure are improved in the light-dark suppression ratio under positive and reverse bias compared to the ultraviolet light detector with the FTO / TiO2 structure.

[0038] like Fig. 9 As shown in the figure, the current-voltage characteristics of the ultraviolet light detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction show that under positive and reverse bias, the dark current is reduced and the photocurrent is increased. The TiO2:PEO / MAPbCl3 heterojunction can greatly improve the performance of the ultraviolet light detector, which indicates that the ultraviolet light detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction has the best performance. DETAILED DESCRIPTION

[0039] Embodiment 1:

[0040] (1) Substrate processing

[0041] The FTO substrate was immersed in acetone, ethanol, and deionized water for ultrasonic treatment for 15 minutes, dried with nitrogen, and then placed in an ultraviolet ozone environment for treatment for 15 minutes to obtain a clean FTO substrate;

[0042] (2) Preparation of TiO2 one-dimensional nanorod array thin films on FTO surface using polar directional hydrothermal method

[0043] At room temperature, 10 mL of toluene was added to the reactor, and 1 mL of tetrabutyl titanate was measured and dripped in dropwise, while the reactor was shaken to disperse the tetrabutyl titanate in the toluene; 0.2 mL of titanium tetrachloride was measured with a syringe and slowly added to the above solution below the liquid surface to make it evenly dispersed; 1 mL of hydrochloric acid with a mass fraction of 37% was measured and dripped into the above solution dropwise; the FTO surface of the substrate was tilted downward and placed in the reactor to fix it, and the reactor was sealed, and the hydrothermal reaction was carried out at 180°C for 5 hours, and then the substrate was taken out after naturally cooling to room temperature, and naturally dried in the air at room temperature, thereby obtaining a 2.5 μm thick TiO2 one-dimensional nanorod array film on the FTO surface;

[0044] (3) Preparation of Ag electrode

[0045] Ag conductive glue was dropped on the FTO and TiO2 nanorod array films respectively as Ag electrodes with a thickness of 2 mm, and then dried at 75°C for 15 minutes to obtain an ultraviolet detector based on the FTO / TiO2 structure.

[0046] After the UV photodetector was prepared, its UV photodetection performance was tested. Figure 7 As shown, under 2V positive bias, the dark current is 3.98×10 -5 A, the photocurrent is 2.083×10 -4 A, the light-dark suppression ratio is 5.234; under -2V reverse bias, the dark current is 1.09×10 -4 A, the photocurrent is 1.359×10 -4 A, the light-dark suppression ratio is 1.247. This shows that there is room for improvement in UV detectors based on FTO / TiO2 structure.

[0047] Embodiment 2:

[0048] (1) Substrate processing

[0049] The FTO substrate was immersed in acetone, ethanol, and deionized water for ultrasonic treatment for 15 minutes, dried with nitrogen, and then placed in an ultraviolet ozone environment for treatment for 15 minutes to obtain a clean FTO substrate;

[0050] (2) A TiO2 one-dimensional nanorod array film was prepared on the FTO surface by a polar directional hydrothermal method, and the specific operation was the same as in Example 1;

[0051] (3) Interface modification of TiO2 one-dimensional nanorod array films using PEO

[0052] The device obtained in step (2) is placed in ultraviolet ozone for 15 minutes to perform hydroxylation on the surface of the TiO2 one-dimensional nanorod array film; 0.04 g of PEO is dissolved in 20 mL of deionized water and ultrasonicated until completely dissolved; the PEO solution is spin-coated on the surface of the hydroxylated TiO2 one-dimensional nanorod array film at a spin-coating speed of 2000 rpm for 25 seconds; then the substrate is dried at 85° C. for 8 minutes and then cooled to room temperature, thereby obtaining a 25 nm PEO interface modification layer on the surface of the TiO2 one-dimensional nanorod array film;

[0053] (4) Preparation of Ag electrode: Ag conductive glue was dropped on the FTO and PEO interface modification layers as Ag electrodes, and then dried at 75°C for 15 minutes to obtain a UV detector based on the FTO / TiO2:PEO structure.

[0054] After the UV photodetector was prepared, its UV photodetection performance was tested. Figure 8 As shown, under the forward bias voltage of 2V, the dark current is 5.98×10 -6 A, photocurrent is 2.59×10 -3 A, the light-dark suppression ratio is 433.11; under the reverse bias voltage of -2V, the dark current is 5.348×10 -7 A, the photocurrent is 1.194×10 -4 A, the light-dark suppression ratio is 223.26, which is significantly improved compared to the FTO / TiO2 structure. The addition of PEO interface modification to the TiO2 one-dimensional nanorod array can reduce the surface work function of the TiO2 film, thereby reducing the electron transfer barrier near the interface, promoting charge transfer between interfaces and reducing charge recombination. The TiO2:PEO film enhances the electron extraction ability of the TiO2 film and effectively improves the electron mobility inside the device.

[0055] Embodiment 3:

[0056] (1) Substrate processing

[0057] The FTO substrate was immersed in acetone, ethanol, and deionized water for ultrasonic treatment for 15 minutes, dried with nitrogen, and then placed in an ultraviolet ozone environment for treatment for 15 minutes to obtain a clean FTO substrate;

[0058] (2) a TiO2 one-dimensional nanorod array thin film was prepared on the FTO surface by a polar directional hydrothermal method, which was the same as in Example 1;

[0059] (3) using PEO to modify the interface of the TiO2 one-dimensional nanorod array film, the details are the same as in Example 2;

[0060] (4) Preparation of MAPbCl3 precursor solution:

[0061] At room temperature, 1 mL DMSO and 1 mL DMF were measured and mixed, and then 0.135 g MACl was weighed and added to the above solution and stirred for 15 minutes; 0.566 g PbCl2 was weighed and added to the above solution, and stirred for 30 minutes until the solution became completely transparent to obtain MAPbCl3 precursor solution, which was then transferred to a new sample bottle for use;

[0062] (5) Preparation of TiO2:PEO / MAPbCl3 heterojunction

[0063] The MAPbCl3 precursor solution was spin-coated on the surface of the PEO interface modification layer to form a 400 nm thick polycrystalline perovskite MAPbCl3 film, the spin-coating speed was 2500 rpm, and the spin-coating time was 25 seconds; then the speed was adjusted to 1200 rpm, and 45 μL of toluene was immediately spin-coated on the polycrystalline perovskite MAPbCl3 film as an anti-solvent, and the spin-coating time was 4 seconds; then the substrate was dried at 80°C for 5 hours and then cooled to room temperature; thereby a TiO2:PEO / MAPbCl3 heterojunction was obtained on the surface of the FTO substrate;

[0064] (6) Preparation of Ag electrode: Ag conductive glue was dropped on FTO and polycrystalline perovskite MAPbCl3 film as Ag electrode, and then dried at 75°C for 15 minutes to obtain a UV detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction.

[0065] After the UV photodetector was prepared, its UV photodetection performance was tested. Fig. 9 As shown, under the positive bias voltage of 2V, the dark current is 4.721×10 -9 A, photocurrent is 2.76×10 -3 A, light-dark suppression ratio is 584745; under reverse bias voltage -2V, dark current is 2.69×10 -10 A, the photocurrent is 1.632×10 -4 A, the light-dark suppression ratio is 606691, which is greatly improved compared with the UV detectors in Examples 1 and 2. The one-dimensional TiO2 nanorod array is a vertical structure, and the polycrystalline perovskite MAPbCl3 film is a planar structure. When irradiated with ultraviolet light, the transmission of photogenerated electrons passes through the TiO2 nanorod array vertically downward to the Ag electrode on the FTO substrate, while the transmission of photogenerated holes passes through the Ag electrode on the MAPbCl3 film, effectively realizing the separation and transmission of photogenerated carriers. PEO not only enhances the electron extraction ability of the TiO2 layer, promotes charge transfer between the TiO2 film and the MAPbCl3 film and reduces charge recombination, but also improves the contact characteristics of the TiO2 film and the MAPbCl3 film, making the contact closer.

[0066] The ultraviolet detector based on the FTO / TiO2:PEO / MAPbCl3 heterojunction prepared by the present invention has the advantages of high light-dark suppression ratio and can effectively detect ultraviolet rays in the UVA region. At the same time, the process of the present invention is simple, the ultraviolet photoelectric detector prepared is small in size, and is suitable for mass production, so it has important application value. The preparation method of the present invention has the characteristics of simple preparation method, low cost, high light response, and promising large-scale production, and has good detection performance for ultraviolet light.

[0067] The above-described contents are only specific implementation modes of the present invention and cannot be used to limit the scope of implementation of the present invention. All equivalent changes and improvements made according to the scope of the patent application of the present invention should still fall within the scope covered by the patent of the present invention.

Claims

1. A UV detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction, characterized in that: From bottom to top, it consists of an FTO substrate (1), a TiO2 one-dimensional nanorod array film grown on FTO (2), a PEO interface modification layer (3) spin-coated on the TiO2 nanorod array film, a polycrystalline perovskite MAPbCl3 film (4) spin-coated on the PEO interface modification layer, and an Ag electrode (5) prepared on the polycrystalline perovskite MAPbCl3 film. The TiO2 one-dimensional nanorod array film (2), the PEO interface modification layer (3) and the polycrystalline perovskite MAPbCl3 film 3 films (4) constitute a TiO2:PEO / MAPbCl3 heterojunction photosensitive layer, and the ultraviolet light to be measured is incident from one side of the FTO substrate (1); wherein the thickness of the FTO substrate (1) is 2~3mm, the thickness of the TiO2 one-dimensional nanorod array film (2) is 2~3μm, the thickness of the PEO interface modification layer (3) is 20~30nm, the thickness of the polycrystalline perovskite MAPbCl3 film (4) is 300~500nm, and the thickness of the Ag electrode is 1~3mm.

2. The preparation of a UV detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction as claimed in claim 1, wherein the steps are as follows: (1) Substrate processing The FTO substrate was immersed in acetone, ethanol, and deionized water for ultrasonic treatment for 10 to 20 minutes, then dried with nitrogen, and then placed in an ultraviolet ozone environment for treatment for 10 to 20 minutes to obtain a clean substrate; (2) Preparation of TiO2 one-dimensional nanorod array films At room temperature, add 8-15 mL of toluene to a reactor, measure 0.5-1.5 mL of tetrabutyl titanate and drip it dropwise, and at the same time shake the reactor to disperse the tetrabutyl titanate in the toluene; measure 0.1-0.3 mL of titanium tetrachloride and slowly add it below the liquid surface of the above solution to prevent the titanium tetrachloride from volatilizing and to make it evenly dispersed; then measure 0.5-1.5 mL of hydrochloric acid with a mass fraction of 36-38%, and drip it dropwise into the above solution; place the FTO surface of the substrate cleaned in step (1) into the reactor with the FTO surface tilted downward, immerse it below the liquid surface of the solution, and fix it, seal the reactor, and hydrothermally react at 150-200° C. for 4-8 hours. After naturally cooling to room temperature, take out the substrate and naturally air-dry it in air at room temperature, thereby obtaining a 2-3 μm thick TiO2 one-dimensional nanorod array film on the FTO surface; (3) Interface modification of TiO2 one-dimensional nanorod array films by PEO The device obtained in step (2) is irradiated in ultraviolet ozone for 10 to 30 minutes to perform hydroxylation on the surface of the TiO2 one-dimensional nanorod array film; 0.02 to 0.12 g of PEO is dissolved in 10 to 50 mL of deionized water and ultrasonicated until completely dissolved; the PEO solution is spin-coated on the surface of the TiO2 one-dimensional nanorod array film after the hydroxylation treatment; then, the PEO solution is dried at 80 to 100° C. for 5 to 10 minutes, and the FTO substrate is cooled to room temperature, thereby obtaining a 20 to 30 nm thick PEO interface modification layer on the surface of the TiO2 one-dimensional nanorod array film; the spin coating speed is 1500 to 2500 rpm, and the spin coating time is 20 to 40 seconds; (4) Preparation of MAPbCl3 precursor solution At room temperature, 0.5-2 mL DMSO and 0.5-2 mL DMF were weighed and mixed, 0.1-0.2 g MACl was weighed and added and stirred for 10-30 minutes; then 0.4-0.6 g PbCl2 was weighed and added and stirred for 20-40 minutes until the solution became completely transparent, thereby obtaining a MAPbCl3 precursor solution; (5) Preparation of TiO2:PEO / MAPbCl3 heterojunction A MAPbCl3 precursor solution is spin-coated on the surface of the PEO interface modification layer to form a 300-500 nm thick polycrystalline perovskite MAPbCl3 film; then the rotation speed is reduced, and 40-50 μL of toluene is immediately spin-coated on the polycrystalline perovskite MAPbCl3 film as an antisolvent, and the substrate is cooled to room temperature after drying, thereby obtaining a TiO2:PEO / MAPbCl3 heterojunction on the surface of the FTO substrate; the spin-coating speed is 2000-3500 rpm, and the spin-coating time is 20-40 seconds; the reduced rotation speed is 1000-1500 rpm, and the spin-coating time of the toluene antisolvent is 3-5 seconds; the drying temperature is 70-100°C, and the drying time is 4-8 hours; (6) Preparation of Ag electrode Ag conductive glue was dropped on FTO and polycrystalline perovskite MAPbCl3 layers as electrodes respectively. After drying, a UV detector based on FTO / TiO2:PEO / MAPbCl3 heterojunction was obtained. The drying temperature was 70~120℃ and the drying time was 8~20 minutes.

Citation Information

Patent Citations

  • Optimized perovskite solar cell based on excellent-conductivity oxide

    CN105810832A

  • TiO2 / NPB heterogeneous one-directional nanorod array ultraviolet detector based on self-exhausting effect and preparation method thereof

    CN106910751A

  • Perovskite photovoltaic battery using polyoxyethylene thin film for passivating interface between electron transmission layer and light sensitive layer and preparation method of battery

    CN109830604A